1975
DOI: 10.1246/bcsj.48.596
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Rotation Involving the Tetrahedral Carbon. XIV. Conformational Equilibria and Attractive Interactions in Substituted 9-Benzyltriptycenes

Abstract: Several 9-benzyltriptycene derivatives were prepared by addition of benzynes to 9-benzylanthracenes. Rotation about the C9–Cbenzyl bond of compounds with a substituent at a peri-position to the benzyl group was found to be frozen at low temperatures on the NMR time scale but not at room temperature. In contrast, compounds with two substituents at two peri-positions to the benzyl group showed a frozen rotation about the C9–Cbenzyl bond at room temperature. Distribution of the conformers, as judged from the PMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Possible origins of this attraction include CH−π interactions, dipole(CO)−dipole/quadrupole (arene) interactions, and lp−π interactions. Compounds 2b − d were reported by Oki in 1975, and small attractive interactions were observed . An lp−π interaction was suggested but not confirmed.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Possible origins of this attraction include CH−π interactions, dipole(CO)−dipole/quadrupole (arene) interactions, and lp−π interactions. Compounds 2b − d were reported by Oki in 1975, and small attractive interactions were observed . An lp−π interaction was suggested but not confirmed.…”
Section: Resultsmentioning
confidence: 90%
“…Noncovalent interactions involving aromatic rings are key processes in chemical and biological recognition , and aromatic residue interactions in proteins and cation−π and lone pair (lp)−π interactions. While the concept of attractive lp−π interaction is counterintuitive, this type of attraction was observed as early as 1975 . More recently, crystallographic evidence has been provided for the stabilizing influence of sugar O4‘ (lp)−π (nucleobase) intramolecular interactions and H 2 O (lp)−π (cytosine) interaction in an RNA pseudoknot. , Recent ab initio studies indicate that lp−π interaction is favorable with electron-deficient π-systems. ,, Scheiner has shown that water prefers the lp−π approach instead of the OH−π interaction in the case of the protonated imidazole .…”
Section: Introductionmentioning
confidence: 99%